Sublingual Delivery of Frovatriptan: An Indication of Potential Alternative Route. (29th October 2014) - Verma, Hitesh; Verma, Surajpal; Prasad, Shyam Baboo; Singh, Harmanpreet
Abstract : Frovatriptan, a 5-HT1B and 5-HT1D receptor agonist, is used for the treatment of acute migraine attack. This molecule is classified into second line therapy because of its slow onset of action (peak response obtained after 4 hours of administration) and low bioavailability (25%). Moreover, its therapy is the most costly among all triptans. Attempt has been made in present work to suggest a way out to fasten its onset of action and to enhance its bioavailability. Prepared tablets were evaluated by physicochemical tests, in vitro permeation studies, ex vivo permeation studies, and histopathological studies. Suitable mathematical calculations were performed to calculate the minimum amount of bioavailability that could be enhanced. Tablets containing chitosan (5% w/w) were found to give optimum results. Prepared tablets can double the bioavailability of frovatriptan and can initiate its response within 10 minutes of its administration. Suggestive alternative has the potential to increase the efficacy of frovatriptan for treating acute migraine attack.